An Investigation of Architectural Heritage Design Features On the Formation of Architectural Identity through Globalization - Amjad Hani Gharezeddin; Mohd Fauzi Sedon (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: This research project investigated the formation of the architectural heritage identity in Damascus within the context of globalization by analyzing the architectural principles of Damascus's prevailing architecture in the contemporary era. The research aims to identify the impact of globalization on the formation of heritage identity in terms of design and characteristics. Design/methodology/approach: The research project used studio practice method through studio experimentation and contextual approaches to investigates how architectural heritage contributes and creates the obsession, emotion, aspiration and belief of urban society towards shaping lifestyle in a contemporary culture. Findings: The research project has been successful in examining how globalization technology and the ability of its modern materials have influenced the representation of heritage elements to create a unique heritage architectural identity adapted to the surrounding space and place. Practical implications: The research contributed to raising the awareness of the community to enhance its appreciation of cultural heritage values, and also contribute to highlighting the pursuit of maximum benefit from all aspects of technological development in the architectural work to find new elements for architectural shape that match the new urban societies. Originality/value: This paper is original. Paper type: a Research Paper.